2019
DOI: 10.1016/j.hal.2019.101660
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of the toxic dinoflagellate Alexandrium catenella in Osaka Bay, Japan using a massively parallel sequencing (MPS)-based technique

Abstract: A B S T R A C TSince 2002, blooms of Alexandrium catenella sensu Fraga et al. (2015) and paralytic shellfish toxicity events have occurred almost yearly in Osaka Bay, Japan. To better understand the triggers for reoccurring A. catenella blooms in Osaka Bay, phytoplankton community was monitored during the spring seasons of 2012-2015. Monitoring was performed using massively parallel sequencing (MPS)-based technique on amplicon sequences of the 18S rRNA gene. Dense blooms of A. catenella occurred every year ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 91 publications
0
12
0
Order By: Relevance
“…However, it may provide an overall impression of species/classes relative abundances (Eiler et al 2013;Giner et al 2016;Gran-Stadniczeñko et al 2017;Schenk et al 2019). For example, the relative sequence abundances obtained by HTS-approach have been reported to coincide with the yearly total abundance patterns detected by using light microscopy for the toxin-producing dinoflagellate Alexandrium catenella (Nagai et al 2019). Furthermore, in combination with light microscopy-based counts, the relative sequence abundances may provide a semi-quantitative estimate of cell abundances, which has high relevance for morphologically similar species, e.g.…”
Section: Common/dominant/toxin-producing Species Appearance Patternsmentioning
confidence: 99%
“…However, it may provide an overall impression of species/classes relative abundances (Eiler et al 2013;Giner et al 2016;Gran-Stadniczeñko et al 2017;Schenk et al 2019). For example, the relative sequence abundances obtained by HTS-approach have been reported to coincide with the yearly total abundance patterns detected by using light microscopy for the toxin-producing dinoflagellate Alexandrium catenella (Nagai et al 2019). Furthermore, in combination with light microscopy-based counts, the relative sequence abundances may provide a semi-quantitative estimate of cell abundances, which has high relevance for morphologically similar species, e.g.…”
Section: Common/dominant/toxin-producing Species Appearance Patternsmentioning
confidence: 99%
“…Improved species detection can be achieved by employing high-throughput sequencing (HTS) methods, such as DNA metabarcoding. This approach allows amplifying the gene of interest from a mass collection of organisms or environmental DNA (eDNA) and thus target multiple species simultaneously (Moreno-Pino et al 2018;Nagai 2018;Nagai et al 2019). Metabarcoding has also been applied for investigating the diversity of microalgae, which has uncovered the presence of previously unknown HAB species/genera for the sampling area (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, eDNA metabarcoding has been successfully applied to reveal appearance patterns for several organism groups ranging from bacteria to mammals (Nagai et al 2016;Hirai et al 2017;Sigsgaard et al 2017;Stoeckle et al 2017;Berry et al 2019;Zhang et al 2020;Sildever et al 2021;Alter et al 2022), including the HAB species (Nagai et al 2017(Nagai et al , 2019Sildever et al 2019). As several genes or markers can be amplified from the same sample, co-appearance patterns and associations amongst species and groups can also be investigated (Lima-Mendez et al 2015;Sawaya et al 2019;Djurhuus et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the same area, Akashiwo sanguinea-dominated algal blooms occurred in mid-June 2016, where the number of copepod species and their abundances in the bloom area were significantly less than those in the nonbloom area, which may be in part due to the fact that the dominant species, such as A. sanguinea and Gonyaulax spinifera, can secrete Ichthyotoxins and Yessotoxins, and similar results about biodiversity also showed that there were no significant differences in the biodiversity indices of zooplankton between the bloom and nonbloom areas [50]. However, it is regrettable that the current research on dinoflagellate blooms is often in the form of cross-sectional voyage surveys (Lin et al [13]) or a longer interval sampling method [12,51], and it is difficult to completely monitor the occurrence and disappearance of a bloom. Therefore, further research is needed to verify the possible impacts of the whole HABs process, including those interactions of diatoms and dinoflagellates on the growth conditions of zooplankton as well as the healthy development of marine ecosystems.…”
Section: Discussionmentioning
confidence: 99%